Characterization of tomato accessions for resistance to early blight - Grigolli,José Fernando Jurca (2011)
The purpose of this study was to characterize 50 tomato genotypes of the Vegetable Genebank of the Federal University of Viçosa. They were evaluated together with the controls Débora, Fanny and Santa Clara, in a randomized block design with two replications. The experiment was conducted in a research field of the UFV, from February to May 2007. We evaluated the disease severity, which is the percentage of diseased leaf area. The severity values were transformed into area under the disease progress curve (AUDPC), improving the result visualization. The analysis of variance and grouping of AUDPC means by the Scott-Knott test at 5 % significance were performed. The accessions BGH-2081, BGH-2034, BGH-700, BGH-2057, BGH-2035, BGH-2054, BGH-2018, BGH-2065, BGH-2008, and BGH-2032 had a lower mean AUDPC than the controls and are therefore indicated for future breeding programs.